PTH-033 An ogd too many: investigation of iron deficiency anaemia. (22nd June 2015) - Kotha, S; McLaren, K; Gera, A; Loganayagam, A
Abstract : Introduction: Iron deficiency anaemia (IDA) occurs in 2–5% of adult men and postmenopausal women in the developed world. The most common cause of IDA in men and postmenopausal women is blood loss from the GI tract. The British Society of Gastroenterology recommends that "upper and lower GI investigations should be considered in all postmenopausal female and all male patients, where IDA has been confirmed unless there is a history of significant overt non-GI blood loss". The main aim of this study was to determine if unnecessary oesophagogastroduodenoscopy (OGD) and duodenal biopsies were being performed in patients with the referral indication of iron deficiency anaemia. Method: We reviewed retrospective data collected from ADAM (endoscopy database) at Queen Elizabeth Hospital for a period of 1 year (2013) for all the OGDs and duodenal biopsies undertaken, with the referral indication of IDA. We analysed all the haematology and biochemistry results for these patients from our laboratory system (Win path). The lowest haemoglobin (Hb) result from the 3 months prior to OGD and any haematinic results were recorded. The assessment of anaemia was based on our laboratory Hb ranges of 118–148 g/L for females and 133–167 g/L for males. Those with low mean corpuscular volume (MCV) but no haematinic results were assumed to have IDA in our analysis. Patients with signs of IDA on blood film were also included. Results: 331 patients underwent an OGD during the study period for the referral indication of IDA. All 331 patients had duodenal biopsies taken. 31 patients (9.3%) were not anaemic.161 patients (48.6%) had no evidence of IDA.31 patients (9.3%) had positive findings on duodenal biopsy, but only 7(2%) patients needed active management based on histology (6 had histology consistent with coeliac disease and 1 was positive for giardia) and the other 24 patients had non-specific findings. There were no significant complications in any of our patients. Conclusion: Clearly, a large number of patients (48.6%) who do not have evidence of IDA were undergoing an OGD. None of the patients had any complications from this invasive procedure. The procedure and analysis of duodenal biopsies is a great expense on the health care system (£700/OGD and £33.6/Biopsy). The introduction of a stringent screening system is needed for referrals with IDA to ensure that appropriate patients are undergoing invasive investigations. Disclosure of interest: None Declared.